A multi-function sensor for online detection of contaminants in hydraulic oil. (October 2019) - Shi, Haotian; Zhang, Hongpeng; Ma, Laihao; Zeng, Lin
Abstract: A multi-function sensor based on microfluidic technology is presented. The sensor is mainly composed of a ring silicon steel sheet and a planar coil. The silicon steel sheet can enhance the magnetic field strength of the detection region, so that the magnetization effect and eddy current effect of metal particles are more intense. The silicon steel sheet not only improves the sensitivity of resistance and inductance detection, but also does not increase the noise of detection signal. Resistance method can detect smaller sizes of copper particles, which compensates the deficiency that inductance method has a low ability to detect non-ferromagnetic metal particles. Combining the inductance signals with the resistance signals, 55 μm iron particles and 115 μm copper particles can be detected by the planar coil with 20 turns. Planar coil and silicon steel sheet can form capacitive sensor to capture capacitance signals, we can detect 90 μm water droplets and 170 μm air bubbles in hydraulic oil. This sensor can distinguish and detect a variety of hydraulic oil contaminants, and can be potentially used for real-time detection for health of machines. Highlights: Multi-contaminants in hydraulic oil can be detected in this sensor. The detection sen sitivity is improved by adding silicon steel sheet. Smaller sized non-ferromagnetic metal particles can be detected by resistance method.